2010
DOI: 10.1176/ps.2010.61.11.1099
|View full text |Cite
|
Sign up to set email alerts
|

Web-Based Psychoeducational Intervention for Persons With Schizophrenia and Their Supporters: One-Year Outcomes

Abstract: These findings suggest that online delivery of psychotherapeutic treatment and educational resources to consumers' homes has considerable potential to improve consumer well-being and offers several advantages over standard clinic-based delivery models.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

4
187
0
8

Year Published

2013
2013
2018
2018

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 159 publications
(199 citation statements)
references
References 27 publications
4
187
0
8
Order By: Relevance
“…Two of the included studies examined the acceptability/use of online-based interventions and 9 provided data on intervention effects. The interventions evaluated consisted of web-based psycho-education (Valimaki et al, 2008;Yakirevitch et al, 2010;Steinwachs et al, 2011;Anttila et al, 2012); web-based psycho-education plus moderated forums for patients and supporters (Glynn et al, 2010;Rotondi et al, 2010); Fig. 1.…”
Section: Resultsmentioning
confidence: 99%
See 3 more Smart Citations
“…Two of the included studies examined the acceptability/use of online-based interventions and 9 provided data on intervention effects. The interventions evaluated consisted of web-based psycho-education (Valimaki et al, 2008;Yakirevitch et al, 2010;Steinwachs et al, 2011;Anttila et al, 2012); web-based psycho-education plus moderated forums for patients and supporters (Glynn et al, 2010;Rotondi et al, 2010); Fig. 1.…”
Section: Resultsmentioning
confidence: 99%
“…It used video tutorials, interactive games and quizzes to enhance engagement and an anonymous social feed or forum Delivery: Sessions took place in offices at the mental health centers integrated web-based therapy, social networking and peer and expert moderation (Alvarez-Jimenez et al, 2013); web-based CBT (Gottlieb et al, 2013); personalized advice based on routine clinical monitoring (van der Krieke et al, 2012), and mobile-based interventions (Spaniel et al, 2008a;Granholm et al, 2012;Spaniel et al, 2012). Six interventions were evaluated in admission units or controlled environments (Valimaki et al, 2008;Yakirevitch et al, 2010;Steinwachs et al, 2011;Anttila et al, 2012;van der Krieke et al, 2012;Gottlieb et al, 2013) and 6 were delivered remotely in real world settings via Internet enabled or mobile devices (Spaniel et al, 2008a;Glynn et al, 2010;Rotondi et al, 2010;Granholm et al, 2012;Spaniel et al, 2012;Alvarez-Jimenez et al, 2013). Table 1 depicts the characteristics of the selected studies.…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…IMR-Web adds to a quickly growing body of literature demonstrating feasibility, acceptability and validity of computerized assessment (Wolford et al, 2008) and treatment methods (Brunette et al, 2011;Drake et al, 2010;Rotondi et al, 2010;Rotondi et al, 2007) for people with SMI. Consumer response to these technologies has been favorable (Wolford et al, 2008), and studies have shown that computerized forms of mental health intervention are at least equally as effective as those that occur "in-person" (Brunette et al, 2011;Rotondi et al, 2010). In addition, consumers who use computerized programs that combine assessment and education prior to medication appointments have reported improved communication with their physician (Chinman et al, 2007;Deegan, Rapp, Holter, & Riefer, 2008).…”
mentioning
confidence: 99%